Classification of the European marsh vegetation (Phragmito‐Magnocaricetea) to the association level. Issue 2 (15th March 2020) - Landucci, Flavia; Šumberová, Kateřina; Tichý, Lubomír; Hennekens, Stephan; Aunina, Liene; Biță‐Nicolae, Claudia; Borsukevych, Lyubov; Bobrov, Alexander; Čarni, Andraž; Bie, Els De; Golub, Valentin; Hrivnák, Richard; et al.
Abstract: Aims: To create a comprehensive, consistent and unequivocal phytosociological classification of European marsh vegetation of the class Phragmito‐Magnocaricetea . Location: Europe. Methods: We applied the Cocktail method to a European data set of 249, 800 vegetation plots. We identified the main purposes and attributes on which to base the classification, defined assignment rules for vegetation plots, and prepared formal definitions for all the associations, alliances and orders of the class Phragmito‐Magnocaricetea using formal logic. Each formula consists of the combination of "functional species groups", cover values of individual species, and in the case of high‐rank syntaxa also of "discriminating species groups" created using the Group Improvement (GRIMP) method. Results: The European Phragmito‐Magnocaricetea vegetation was classified into 92 associations grouped in 11 alliances and six orders. New syntaxa (previously invalidly published according to the International Code of Phytosociological Nomenclature) were introduced: Bolboschoeno maritimi‐Schoenoplection tabernaemontani, Glycerio maximae‐Sietum latifolii, Glycerio notatae‐Veronicetum beccabungae, Schoenoplectetum corymbosi and Thelypterido palustris‐Caricetum elongatae. Based on a critical revision, some other syntaxa were rejected or excluded from the class Phragmito‐Magnocaricetea . Conclusions: This work provides the first consistent classification of the class Phragmito‐Magnocaricetea at the European scale, which is an important tool for nature conservation. Our classification largely respects previously existing concepts of syntaxa, but it also proposes modifications to the recently published EuroVegChecklist. This work also provides a protocol that can be used for extending the current classification to new syntaxa and geographical regions. Abstract : This paper presents a comprehensive and formalized classification of European marsh vegetation. The work is based on more than 200, 000 vegetation plots and provides a consistent protocol and a hierarchic expert system for the classification of 92 phytosociological associations, 11 alliances and six orders of Phragmito‐Magnocaricetea class.